Genetic variance and correlation of forage yield and quality traits in tropically adapted maize - Nazatul Shima Naharudin,; Maizura Abu Sin,; Ghizan Saleh, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Two F2 populations segregating for biomass yield and forage quality traits were developed from two separate crosses of tropically adapted maize inbred lines. The parental, F1 and F2 generations of both crosses were evaluated to estimate broad sense heritability, genetic advance and correlations for these traits to suggest the best traits as selection criteria towards breeding forage maize with high yield and quality. In Cross 1, biomass yield trait with the highest broad-sense heritability was plant height (70.03%), whereas forage quality trait with the highest heritability estimate was crude protein content (66.60%). Heritability estimates in Cross 2 were high for all biomass yield traits and forage quality traits (>50% for all traits). Indigestible cell wall component represented by acid detergent lignin content was found to be highly heritable in both populations. High genetic advance as percent of mean were found for fresh and dry plant yield as well as for lignin content in both populations. Correlation analysis on all traits showed that all biomass yield components were significantly correlated. All traits related to cell wall content were positively correlated and acid detergent lignin was positively correlated with dry plant yield. Traits with high to moderate heritability and high predicted genetic advance, namely plant height, fresh plant yield and protein content can be used as selection criteria to improve maize biomass yield and nutritive quality for forage utilization. Selecting for higher biomass yield would also result in selecting individuals with higher lignin content as shown by the correlation analysis.